Survey on the effectiveness of learning the crouching start technique on short distance running learning - Samsul Arifin; Taufik Rahman; Abdul Aziz (Sriwijaya Journal of Sport)
The purpose of this study was to investigate the implementation of online physical education learning at SDN Gayam II in the Sapudi Islands, Sumenep Regency. The research data was obtained from the results of interviews with physical education teachers, students, and parents, as well as the results of direct observations made by researchers. The results showed that: 1) the problems with the internet network were not good in the Sapudi Islands; 2) low economic constraints, this causes not all students and guardians of students to have android mobile phones (HP); and 3) there are some parents who cannot help supervise online learning. So it can be concluded that educational learning at SDN Gayam II Sapudi Islands, Sumenep Regency is less and even tends to be ineffective.